Medication Adherence And Its Associated Factor: A Cross-Sectional Study Among Patients with Schizophrenia - Noor U Saba; Sushma Muraraiah (Pharmacology and Clinical Pharmacy Research, 2022)
Schizophrenia is a chronic severe psychiatric disorder. Antipsychotic medications are a highly efficacious modality of treating patients with schizophrenia. Non-adherence to antipsychotic medication is a critical problem leading to increased relapse rate, hospitalization rate, and health care costs. Non-adherence is caused by multi-factors and might be varied within the globe. Assessing non-adherence and influencing factors would help in framing preventive strategies. This cross-sectional study involved 100 patients with schizophrenia fulfilling inclusion criteria. Patients’ demographics, clinical parameters, and prescribed drugs were collected. Medication adherence was assessed using the MARS scale (medication adherence rating scale) and symptom severity by PANSS (positive and negative symptom scale). Statistical analysis was done to identify the potential predictors of non-adherence to antipsychotic medication. The correlation of medication adherence with severity of illness was tested. Males were significantly associated with decreased likelihood of being non-adherent with odds ratio of 0.095 (0.014, 0.667) p value of 0.018. An increase in positive and cognitive scores was significantly associated with higher odds of being non-adherent with OR of 1.188 (1.044, 1.325) p-value 0.009 and OR 1.258 (1.073, 1.475) p value 0.005. From this study, non-adherence to medication was noted in 45% of the study population. Thus, strategies need to be framed for regular monitoring and follow-up of female patients on antipsychotics and patients with high PANSS. These steps could reduce the frequency of non-adherence among patients with schizophrenia.